Maternal and perinatal outcomes in early versus late onset pre-eclampsia – A comparative study - Nirmita Saha; Sandip Sarkar; Rupali Modak; Lipika Adhikari; Debdatta Ghosh (Asian Journal of Medical Sciences)
Background: Hypertensive disorders are the most common medical complications of pregnancy and complicate up to 10% of pregnancies.